The potential for albedo-induced climate mitigation using no-till management in midwestern U.S. croplands - Xian Wang; Mallory Barnes; Landon Yoder; Christopher Williams; Jennifer Tank; Todd Royer; Shellye Suttles; Kim Novick (Communications Earth & Environment)
Abstract No-till management is often recognized for its environmental and economic benefits, but its potential to reduce climate warming is still uncertain. Beyond ongoing debate over its effects on soil carbon storage, no-till also leaves plant residue on the surface, which can reflect more sunlight. This increase in surface reflectivity, called albedo, may help mitigate climate change by reducing the energy absorbed by the land. Here, we assessed this climate benefit of no-till across the U.S. Corn Belt using conservation survey records, county-level tillage data, and satellite observations. We found that no-till increased land surface brightness during the dormant season, reducing absorbed solar energy by an estimated 50 grams of CO2 equivalent per square meter per year. Regionally, this could add up to 24 teragrams of CO2 equivalent per year in potential climate benefits. Areas with low adoption, especially those with dark, carbon-rich soils, offer the greatest opportunity for further mitigation.